CLIMATE CHANGE AWARENESS AND RISK PERCEPTION AMONG FINANCIAL INSTITUTIONS EMPLOYEES IN KUALA LUMPUR - Auni Zulfaka; Salina Kassim (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Climate change is happening, extreme events related to it are on the rise globally, and Malaysia, for sure, will not be spared from the effects of the phenomenon. For the past few years, numerous studies attempted to explore public awareness and educating the public about climate change. Realising that the global financial industry has started to play an important role in fighting climate change since it interconnects with all sectors, this study was conducted to explore the awareness and risk perception among financial institutions’ employees in Kuala Lumpur. The result found that most of the respondents were acknowledged climate change as a threat to the environment and were also aware of the impacts of climate change on the stability of the financial systems as a whole. Knowledge about climate change seemed to play an important role in creating awareness and risk perception among the financial industry employees. This study’s findings have important implications for Malaysia’s financial institutions so that they are made aware of these issues and able to be ready to support the mandate given by the regulators to effectively frame climate change adaptation strategies as a risk management process. As a result, it is crucial to coordinate outreach programmes and training organised by respective organisations to increase climate change adaptation knowledge levels and enhance employees’ ability to foster climate change understanding and meet a significant portion of the Malaysian public.